The Use of Game Theory for Making Rational Decisions in Business Negations: A Conceptual Model - Kęstutis Peleckis (Entrepreneurial Business and Economics Review)
Objective: The objective of this paper is a comparative analysis of the world literature on game theory and its applicability for rational decision-making in negotiations and creation of a model supporting strategic decisions in negotiations. Research Design & Methods: Systematic, comparative, logical analysis and synthesis of the scientific literature. In order to create an algorithm of negotiations statements on theory of graphs, game theory and theory of heuristic algorithm were applied. Findings: The article proposes an algorithm which combines the game theory approach with heuristic algorithms in order to reflect the specifics of negotiations better. Such an algorithm can be used to support strategic decisions in negotiations and is useful for better understanding of the strategic management of negotiating processes. Implications & Recommendations: The proposed mathematical algorithm for the strategy formulation of international business negotiations can be used in electronic business negotiations, both as a standalone tool, or as partially requiring support by the negotiator. Contribution & Value Added: The game theory methods support rational solutions in business negotiations, as they enable to analyse the interacting forces. This is particularly relevant in international business negotiations, where participants from different cultures can be faced with numerous uncertainties.